Compressive strength of axially loaded circular hollow centrifugal concrete-filled steel tubular short columns. (15th December 2019) - Zhao, Yan-Gang; Yan, Xi-Feng; Lin, Siqi
Highlights: The compressive strengths of HCCFST columns are significantly affected by the column parameters. A new confinement coefficient reflecting the confinement effect of concrete strength is proposed. A novel formula is proposed to predict the compressive strengths of circular HCCFST stub columns. The proposed formula can also be used to predict the compressive strength of circular CFST stub columns. Han's FE model can be used to reasonably predict the axial behavior of circular HCCFST stub columns. Abstract: Circular hollow centrifugal concrete-filled steel tubes (HCCFSTs) are employed widely as structural components, such as power station structures and building foundations, in virtue of their exceedingly good structural performance features. It is essential to comprehend the compressive behavior of circular HCCFST columns and suitably evaluate their compressive strength for practical engineering design. However, limited researches on HCCFST columns have almost not resulted in the development of appropriate design formulae in current international standards. This paper aims to propose a practical formula for estimating the compressive strength of circular HCCFST stub columns that have a wide range of parameters. A new confinement coefficient reflecting the confinement effect of concrete strength in circular HCCFST short columns is proposed, and using the proposed confinement coefficient, a novel strength design formula is developed to estimate the compressive strength of circular HCCFST short columns. The proposed formula is investigated using collected experimental data from literature and finite element analysis results. It is shown that the proposed confinement coefficient can reflect the interaction effect between the steel tube and infilled concrete, and the developed axial capacity formula in this paper offers better predictions of compressive strength than current design formulae.